BELAJAR TOLERANSI DI PONDOK PESANTREN GONTOR PONOROGO - Hasan Bastomi (Institut Agama Islam Negeri Kediri, 2019)
Abstract: In the period 2010-2013 the incidence of intolerance in Indonesia is increasing, not to be added with other rows of cases from 2014 until 2017. Intolerance turmoil in Indonesia heats up as the implementation of actions in the name of defense of religion. Starting from peaceful action 411 to action 212 at the end of 2016 and action 212 volumes II in early 2017. Whereas as the people of Indonesia should keep harmony in the midst of diversity with a tolerance. Tolerance in Islam is more than tolerance or willingness to accept genuine disagreements but it also contains ihsan (goodness) to others who bring love to someone who is given to him goodness, and leads to love, harmony, and keeps people away from violence and alienation . Speaking of tolerance we can learn from the portrait of Pondok Pesantren Gontor Ponorogo. The idea to build Gontor into a boarding school that instilled the values of tolerance originated from the social and political situation of the Indonesian nation also affect the education. The insight of true tolerance has become a basic education that is not only taught in formal teachers in the classroom. But also done in the daily life of santri. The tolerance education at Gontor’s cottage is also reflected in the content or content of the curriculum that clearly teaches the santri’s insight into the diversity of beliefs. In terms of tolerance Pondok Gontor diibarataan as miniature Indonesia there are thousands of students with different backgrounds and races. But with the difference, all students in Gontor can appreciate each other. Abstrak: Dalam kurun waktu 2010-2013 peristiwa intoleransi di Indonesia semakin meningkat, belum ditambah dengan deretan kasus lainnya dari tahun 2014 hingga tahun 2017. Gejolak intoleransi di Indonesia memanas seiring dilaksanakannya aksi yang mengatasnamakan pembelaan agama. Mulai dari aksi damai 411 hingga aksi 212 pada penghujung tahun 2016 dan aksi 212 jilid II di awal tahun 2017. Padahal sebagai masyarakat Indonesia selayaknya menjaga keharmonisan di tengah kebhinekaan dengan sikap toleransi. Toleransi dalam Islam lebih dari sekedar toleransi atau kemauan untuk menerima ketidaksepakatan yang genuine tapi di dalamnya juga terkandung ihsÃ¢n (kebaikan) kepada orang lain yang membawa kecintaan kepada seseorang yang diberikan kepadanya kebaikan, dan mengarahkan pada kecintaan, keharmonisan, serta menjauhkan manusia dari kekerasan dan alienasi. Berbicara tentang toleransi kita bisa belajar dari potret Pondok Pesantren Gontor Ponorogo. Gagasan untuk membangun Gontor menjadi pondok pesantren yang menanamkan nilai-nilai toleransi berawal dari situasi sosial dan politik bangsa Indonesia berpengaruh pula pada pendidikan. Wawasan toleransi sesungguhnya telah menjadi pendidikan dasar yang tidak hanya diajarkan dalam pengajar formal di kelas saja tapi juga dilakukan dalam kehidupan sehari-hari santri. Pendidikan toleransi di pondok Gontor juga tercermin dari muatan atau isi kurikulum yang kentara mengajarkan wawasan santri akan keragaman keyakinan. Dalam hal toleransi Pondok Gontor diibarataan sebagai miniatur Indonesia yang terdapat ribuan santri dengan berbeda latar belakang serta ras. Namun dengan perbedaan tersebut, seluruh santri di Gontor bisa saling menghargai.